Pengaruh Environmental Performance, Environmental Disclosure Return On Asset (ROA) Terhadap Economic Performance - Dwi Rantika Muslim Apriyani (AKT 14 UMY 077, 2014)
77 Environmental Performance, Enviromental Disclosure, Return On Asset (ROA), Economic Performance, Proper.